(untitled) (Third Sector Social Economic Review, 2024)
The purpose of this study is to determine the role of environmental awareness as a mediator in the relationship between green accounting education and perception of green accounting. The scope of the study includes the benefits of green accounting, the relationship between environmental awareness and perception of green accounting, and the importance of green accounting education in developing environmental awareness for people and businesses. In the study, demographic, factor, correlation and regression analyses were used to analyze the data. The results are obtained by a regression analysis consisting of four stages. Firstly, green accounting education had a substantial effect on the perception of green accounting. Secondly, this education also greatly enhances levels of environmental awareness. Thirdly, environmental awareness has a substantial impact on the perception of green accounting. The las one is there exists a partial mediation effect of environmental consciousness on the association between green accounting education and the perception of financial advisers in Şanlıurfa about green accounting. Findings emphasize that green accounting education can have in the corporate industry. Therefore, integrating environmental principles into accounting education can have a substantial impact on attitudes and promote a more sustainable approach to corporate processes, as indicated by the study’s implications.